Association with the Development and Menorracy of Polymorphism Rs2046934 of the P2ry12 Gene in Patients with Dysaggregation Thrombocytopathies. (Global Journal of Medical Research, 2022)
The results of studying the peculiarities of the P2RY12 gene polymorphism (rs2046934) revealed in the main group of road traffic accidents an increase in the proportion of the unfavorable allele A by 2.24 times (χ2=3.61; P=0.06; OR=2.24) in relation to the control, which indicates the presence of a tendency towards the risk of developing disaggregated thrombocytopathies. In addition, there was an increase among patients with NDTP of the mutant genotype A / A (χ2=3.04; P=0.08). Indicates a tendency towards an increased risk of development and associative relationship with the clinic (namely with menorrhagia) (χ2=5.6; P=0.02; OR=4.3) of this disease.
Keywords: polymorphism; allele; unfavorable; genotype; risk of development; menorrhagia